2009
DOI: 10.1593/neo.81508
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal Superantigen-like 10 Inhibits CXCL12-Induced Human Tumor Cell Migration

Abstract: Staphylococcal superantigen-like 10 is a potential lead in the development of new anticancer compounds preventing metastasis by targeting CXCR4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 48 publications
0
47
0
Order By: Relevance
“…SSL7 binds to IgA and C5 (21); SSL5 binds to PSGL-1 (4), chemoattractant receptors (5), and MMP-9 (15), and SSL10 binds to chemokine receptor (32) and human IgG (16,23). Therefore, the SSL family is able to interfere with multiple points of host immunity, especially humoral immunity, opsonization, and trafficking of leukocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSL7 binds to IgA and C5 (21); SSL5 binds to PSGL-1 (4), chemoattractant receptors (5), and MMP-9 (15), and SSL10 binds to chemokine receptor (32) and human IgG (16,23). Therefore, the SSL family is able to interfere with multiple points of host immunity, especially humoral immunity, opsonization, and trafficking of leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that SSL5 binds to matrix metalloproteinase 9 (MMP-9), a member of the zinc-dependent endopeptidase family that is responsible for the degradation of extracellular matrix, and inhibits its proteolytic activity and transmigration of neutrophils through Matrigel basement membrane (15). SSL10 binds to chemokine receptors and inhibits chemotaxis of tumor cells (32). SSL10 also binds to human IgG and inhibits the interaction of IgG with complement C1q and the Fc␥ receptor (16,23).…”
mentioning
confidence: 99%
“…Interestingly, the functions that have been discovered for SSLs so far have all been linked to immune evasion. SSL5 inhibits neutrophil extravasation (17,18) and phagocyte function (19,20), SSL7 binds IgA and inhibits complement (21), and SSL10 inhibits IgG1-mediated phagocytosis (22,23), blood coagulation (24), and the chemokine receptor CXCR4 (25). In addition to SSL3, also weak TLR2 inhibitory activity was observed for SSL4 (5), but it remains unknown whether that is its dominant function.…”
mentioning
confidence: 99%
“…The natural ligand for CXCR4 is CXCL12, but SSL10's action clearly inhibited the chemotactic response of HeLa (cervical carcinoma) cells towards the natural ligand. 70 The class of bacterial protein SSL5 has been demonstrated to bind to the receptor for P-selectin glycoprotein-1 (PSGL-1), inhibiting rolling of neutrophils on a surface by acting as a decoy and thus hampering the interaction with its natural ligand, the P-selectin. The inhibitory action of SSL5, without any observed toxicity, was demonstrated in HL-60 leukemia cells since these cells express the receptor P-selectin glycoprotein-1 (PSGL-1).…”
Section: Bacteria-derived Anticancer Agentsmentioning
confidence: 99%